Dilemas éticos vivenciados pela equipe multiprofissional nas relações de cuidado de pessoas pós Covid-19 - Assis, Thamara Arianny Ventin Amorim Oliveira de (2023)
The ethical dilemmas experienced by the multidisciplinary team are situations in which they are forced to decide between two paths in which neither seems correct. The COVID-19 pandemic highlighted the ethical dilemmas experienced by this team, since the rapid contagion, large number of hospitalizations, lack of hospital infrastructure and the lack of knowledge about the disease imposed decision-making, most of the time, difficult. This is a phenomenological research that aims to understand the ethical dilemmas experienced by the multidisciplinary team in care relationships in a care center for post-COVID-19 people. The research project was approved by the Ethics and Research with Human Beings Committee of the State University of Feira de Santana, with the opinion 5.391.098. Ten professionals participated in the study, including doctors, nurses, physiotherapists who work in the Post-COVID-19 Care Center, through phenomenological interviews. The data were analyzed by the proposal of the situated phenomenon of Martins and Bicudo and supported by the theoretical framework of Maurice Merleau-Ponty. The following empirical categories emerged: Ethical dilemmas in the care of the multidisciplinary team at the Post-COVID Care Center; Deliberation in the mode of care of the multidisciplinary team in the care of people after covid-19; The Multiprofessional Team in the care of people with sequelae of COVID-19; Difficulties experienced by the multidisciplinary team in the care of people after COVID-19; Prevention of ethical dilemmas in the care of people post-COVID-19. The results showed that the participants, despite experiencing ethical dilemmas, are unaware of their meaning. Feelings of fear emerged during the practice and fear of transmitting the disease to their families. The experiences of ethical dilemmas concern people with suicidal ideas, referral of people with respiratory sequelae requiring immediate care, but the unit being outpatient was necessary to request their transfer; women who experienced violence during the pandemic, in addition to bringing reports in the post-pandemic and how the lack of a public health structure hinders the performance of the multidisciplinary team. In relation to doing and acting, the study showed the importance of a good relationship between the multidisciplinary team; experience to carry out the actions and promote service excellence. The participants encounter difficulties in relation to the lack of communication between the Care Center and other health units of the municipal network. Regarding the prevention of ethical dilemmas, the study pointed out that ethics should permeate care, as well as humanization, welcoming and communication. It is concluded that the care of post-Covid-19 people raised ethical dilemmas, related to vaccine refusal, fear of contamination by the virus and reduced studies on the post-COVID-19 sequelae. Good communication between team professionals, as well as holding meetings, roundtables of conversations about people post-Covid-19 makes it possible to prevent ethical dilemmas. A protocol was produced to guide the multidisciplinary team in coping with the prevention of ethical dilemmas in the Post-Covid Care Center.